E os da banda d’alá son máis estranxeiros que os de Madrí? - Calo Lourido, Francisco (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
The history split the old Callaecia in two. Portugal becomes a sovereign state, Galicia fades away in Spain. Galician people had to emigrate, make ungrateful works and they were despised. Today Galicia-Portugal relations are nonexistent or, when existing, they are asymmetric.